THE ROLE OF AUDIT QUALITY IN ACHIEVING SUSTAINABLE DEVELOPMENT- AN APPLIED STUDY IN INSURANCE COMPANIES - Sajjad Yahya Ali Zirjawi; Anis Ben Amar, Professor on Accounting (Scholar Express Journals, 2024)
The quality of auditing is a necessity imposed by life on companies, especially in light of the circumstances in which the conflict of interests of the actors in economic operations arose, whether they are investors, workers or managers in those companies, and the purpose of adopting this concept is to fight financial and administrative corruption, and reduce the state of conflict between the parties dealing with economic units, and that one of the most important pillars on which the quality of audit is built is transparency and credibility of reports published by companies, Hence, the role of auditing emerges as a neutral body that works to increase the credibility of reports by conducting a high-quality audit process in order to provide appropriate information and raise the degree of reliability to achieve sustainable development, hence the objective of the study is to urge the concerned authorities to issue laws and legislation regulating accounting and auditing work, which leads to raising the quality of financial reports and then applying audit quality standards in the Iraqi public units in general and the research sample units in particular. Developing the performance of accounting offices in the Republic of Iraq with the provision of some guidelines to government agencies and associations organizing the profession helps to find effective professional control over auditing accounts to promote sustainable development in institutions, and their reflection in achieving sustainable development
Keywords: Quality of Auditing; Sustainable Development; Governance